Chasing the ghosts: stories of people left behind on the frontline of climate and ecological crisis. (December 2022) - Rai, Ayushi
Human-induced global climate change is associated with population migration as places become uninhabitable. Uttarakhand is one of India's most ecologically fragile and climatically vulnerable states. There are massive disparities between the hill and the plain districts as the development initiatives remain concentrated in the plain districts. The inadequacy of the state government, coupled with environmental changes, has made the life of the hill communities challenging. Many people have migrated from the hills resulting in depopulated or ghost villages. Based on interviews with 75 people, the article attempts to shed light on changes that occur when the inhabitants of a place leave. Loss of a place and its community life can have severe implications on the well-being of the people. Respondents showed a range of emotions, including the longing for their homes before the onset of environmental changes. With more intense and frequent climatic events, it has become essential to understand such social and cultural costs of migration.